2023
DOI: 10.5006/4234
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study on the Effects of Key Influencing Factors on a Pull-Off Adhesion Test of Organic Coatings

Abstract: Coatings can protect metallic substrates (e.g., piping, vessels, tubes, etc.) against corrosion attack. The adhesion strength of a coating to its substrate is an essential factor that defines the overall coating integrity and performance. A pull-off adhesion test is commonly performed to determine the coating adhesion strength. This study evaluated the effect of various vital influencing factors on the pull-off adhesion test, including surface preparation of the loading fixture (dolly) and coating surface, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The area fractions of certain failure modes (cohesion, adhesion, and glue) of the detached adhesive surfaces after pull-off tests were calculated using ImageJ software, version 1.52t [17]. Cohesion is defined as the internal strength of an adhesive resulting from the various interactions within the adhesive (single material), while adhesion refers to the bonding between the coating and metal substrate (two materials).…”
Section: Pull-off Adhesion Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The area fractions of certain failure modes (cohesion, adhesion, and glue) of the detached adhesive surfaces after pull-off tests were calculated using ImageJ software, version 1.52t [17]. Cohesion is defined as the internal strength of an adhesive resulting from the various interactions within the adhesive (single material), while adhesion refers to the bonding between the coating and metal substrate (two materials).…”
Section: Pull-off Adhesion Strengthmentioning
confidence: 99%
“…As the pull-off adhesion tests measure the weakest bond among the coating/steel, coating, and coating/dolly, the results indicated that the bond strength between the coating/substrate increased after thermal exposure. The area fractions of certain failure modes (cohesion, adhesion, and glue) of the detached adhesive surfaces after pull-off tests were calculated using ImageJ software, version 1.52t [17]. Cohesion is defined as the internal strength of an adhesive resulting from the various interactions within the adhesive (single material), while adhesion refers to the bonding between the coating and metal substrate (two materials).…”
Section: Pull-off Adhesion Strengthmentioning
confidence: 99%